The contribution of emotional empathy to approachability judgments assigned to emotional faces is context specific - Willis, Megan L.; Lawson, Danielle L.; Ridley, Nicole J.; Koval, Peter; Rendell, Peter G. (Frontiers in Psychology, 2015)
Previous research on approachability judgements has indicated that facial expressions modulate how these judgements are made, but the relationship between emotional empathy and context in this decision-making process has not yet been examined. This study examined the contribution of emotional empathy to approachability judgements assigned to emotional faces in different contexts. One hundred and twenty female participants completed the Questionnaire Measure of Emotional Empathy. Participants provided approachability judgements to faces displaying angry, disgusted, fearful, happy, neutral and sad expressions, in three different contexts – when evaluating whether they would approach another individual to: 1) receive help; 2) give help; or 3) when no contextual information was provided. In addition, participants were also required to provide ratings of perceived threat, emotional intensity and label facial expressions. Emotional empathy significantly predicted approachability ratings for specific emotions in each context, over and above the contribution of perceived threat and intensity, which were associated with emotional empathy. Higher emotional empathy predicted less willingness to approach people with angry and disgusted faces to receive help, and a greater willingness to approach people with happy faces to receive help. Higher emotional empathy also predicted a greater willingness to approach people with sad faces to offer help, and more willingness to approach people with happy faces when no contextual information was provided. These results highlight the important contribution of individual differences in emotional empathy in predicting how approachability judgements are assigned to facial expressions in context.